Rancang Bangun Prototype Kelembaban Tanah - Imam Mahdi; Dian Kasoni (LPPM STMIK ANTAR BANGSA, 2019)
AbstractÃ¢â‚¬â€Apart from its name as a maritime country, Indonesia is also an agricultural country with fertile land and it has 2 seasons, rainy and dry. In the rainy season, food crops are usually not necessary to be watered because they already have received enough water. But in the dry season, they must be regularly watered because of the soil moisture conditions. The dependence of farmers on these seasons causes the production of farmers to decrease and become an obstacle to soil moisture. To overcome these obstacles and make farmers can still plant crops in the dry season, a product of information and communication technology-based agricultural equipment is needed. It is a programmable microcontroller chip that can automatically control plants watering based on soil moisture detected using soil moisture sensors. The development method used in this study is the prototype model and the programming language used is Arduino. The purpose of the tool is to detect whether the planting ground is dry so that the device can control watering automatically when the soil lacks water. This prototype was applied to realize a smart garden in utilizing technological advancements.